2006
DOI: 10.1056/nejmoa050580
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Role of Tumor Necrosis Factor α in Refractory Asthma

Abstract: Patients with refractory asthma have evidence of up-regulation of the TNF-alpha axis. (ClinicalTrials.gov number, NCT00276029.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
520
4
18

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 766 publications
(559 citation statements)
references
References 27 publications
17
520
4
18
Order By: Relevance
“…We are, however, unable to examine the effect of in utero cigarette smoke exposure, which is a risk factor for both depression and asthma in the offspring (43,44). Depression is also associated with high systemic levels of inflammatory cytokines, particularly TNFa, which, in turn, has a pathogenic role in asthma (45,46). Finally, a potential neuroendocrine mechanism involves depression-related alteration in the hypothalamic-pituitary-adrenal axis that For definition of abbreviation, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…We are, however, unable to examine the effect of in utero cigarette smoke exposure, which is a risk factor for both depression and asthma in the offspring (43,44). Depression is also associated with high systemic levels of inflammatory cytokines, particularly TNFa, which, in turn, has a pathogenic role in asthma (45,46). Finally, a potential neuroendocrine mechanism involves depression-related alteration in the hypothalamic-pituitary-adrenal axis that For definition of abbreviation, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…This action of TNF␣ may contribute in part to the airway hyperresponsiveness induced by this cytokine. intracellular calcium; pulmonary afferent; transient receptor potential vanilloid type 1; airway inflammation; asthma AN IMPORTANT ROLE OF TNF␣ in the pathogenesis of allergic asthma has been extensively documented (6,9,28,47). TNF␣ can be released from a variety of cell types in the airways, particularly macrophages, monocytes, and mast cells.…”
mentioning
confidence: 99%
“…AN IMPORTANT ROLE OF TNF␣ in the pathogenesis of allergic asthma has been extensively documented (6,9,28,47). TNF␣ can be released from a variety of cell types in the airways, particularly macrophages, monocytes, and mast cells.…”
mentioning
confidence: 99%
“…Regarding the role of TNF-a in human asthma, TNF-a has been reported to induce epithelial apoptosis and shedding [27]. Additionally, recent studies have demonstrated that anti-TNF-a therapy in patients with asthma markedly improved asthma symptoms, lung function, and AHR, in which the most striking feature of anti-TNF therapy was the improvement in AHR [28,29], further indicating an important role of TNF-a in the development of AHR.…”
Section: Discussionmentioning
confidence: 99%